EFEKTIFKAH FIRM SIZE MEMODERASI HUBUNGAN ANTARA INTELLECTUAL CAPITAL DENGAN KINERJA KEUANGAN PERUSAHAAN - Putu Atim Purwaningrat; Luh Nik Oktarini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The purpose of this study was to determine the effect of intellectual capital on the company's financial performance and the influuence of firm size as a moderating variable between intellectual capital and the financial performance of the consumption sector companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The sampling technique uses purposive sampling technique with a total of 120 companies. The results of the analysis based on statistical tests that intellectual capital has a positive effect on the company's financial performance and firm size succeeded in moderating the relationship of intellectual capital with the financial performance of the consumption sector companies on the Indonesia Stock Exchange